2001
DOI: 10.1097/00006454-200102000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cytomegalovirus infection in preterm and full-term newborn infants from a population with a high seroprevalence rate

Abstract: The frequency of congenital CMV infection in preterm newborn infants from mothers with a high seropositive rate was similar to that found in term infants. No significant difference was found between the proportion of symptomatic infants among preterm and term infants. Our finding of symptomatic congenital CMV infection underscores the need of further evaluation of correlates of congenital symptomatic infection in highly immune populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 20 publications
6
54
1
4
Order By: Relevance
“…The incidence of CI varies between 0.2% and 2.5% in all live births in both preterm and full-term newborns [3,4]. Several studies of PI, mainly in preterm infants, have shown a wide range of prevalence, from 5% to 50% [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of CI varies between 0.2% and 2.5% in all live births in both preterm and full-term newborns [3,4]. Several studies of PI, mainly in preterm infants, have shown a wide range of prevalence, from 5% to 50% [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of infection increases with age, and is higher for those with a lower socioeconomic status, and people living in developing countries. Congenital CMV infection occurs in approximately 0.2 to 2.4% of all live births [5][6][7]. Perinatal infection occurs more frequently than congenital infection and thus many more are infected within the first year.…”
Section: Introductionmentioning
confidence: 99%
“…In France, the rate of congenital infection is also in this range, approximately 1% [2]. In Brazil, studies showed prevalence from 2.1% [3] to as high as 6.2% [4]. Generally, 10% of infected children are symptomatic, while 85-90% are asymptomatic.…”
mentioning
confidence: 99%